(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
Through this report I present the steps taken to a process of research and construction of a collaborative artistic work. It started from an experimental base of researching in conjunction with the project of Laboratório Transdisciplinar de Cenografia (LTC) in search of a joint expression that linked the cordel narrative to the lighting aiming to build a multimedia work in a scenic miniature box.